2023
DOI: 10.1039/d3lc00052d
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation-independent ultrafast laser selective etching processing in fused silica

Abstract: In fused silica, ultrafast laser assisted etching enables high chemical etching rates (>300 μm·h-1) by setting the light polarisation linear and perpendicular to the beam writing direction. However, for many...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Among the possible etchants for FLICE, aqueous solutions of NaOH have been recently appointed as the ones showing the highest etching selectivity, with etching rates >300 μm/h of the irradiated tracks 10,11 . In previous works 9,10,11 , etching in alkaline solutions is usually performed at temperature equal or higher than 85 °C, resulting in the erosion of the unirradiated material of the order of few hundreds of nanometer per hour. This value, while suitable for creating micrometric channels with significant aspect ratios, is still too high to achieve the goal of creating nanometric-diameter channels.…”
Section: Etching Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the possible etchants for FLICE, aqueous solutions of NaOH have been recently appointed as the ones showing the highest etching selectivity, with etching rates >300 μm/h of the irradiated tracks 10,11 . In previous works 9,10,11 , etching in alkaline solutions is usually performed at temperature equal or higher than 85 °C, resulting in the erosion of the unirradiated material of the order of few hundreds of nanometer per hour. This value, while suitable for creating micrometric channels with significant aspect ratios, is still too high to achieve the goal of creating nanometric-diameter channels.…”
Section: Etching Conditionsmentioning
confidence: 99%
“…Among those, type II modifications are the one of interest for FLICE, since they allow the creation of arbitrary shaped three-dimensional hollow structures in the bulk of the material, by simply moving the laser focus with respect to the sample and adequately tailoring the etching process. Common etchant for FLICE are Hydrofluoric acid (HF), which shows etching rates of ∽300 μm/h of the irradiated tracks, up to two times faster than the pristine material 8 , and alkaline aqueous solution containing a certain concentration of potassium hydroxide (KOH) or sodium hydroxide (NaOH), with some authors having recently demonstrated that is possible to achieve etching rates similar to or even higher than those of HF, ensuring greater etching contrast and employing solutions that are less hazardous and have a lower environmental impact 9,10,11 .The reasons behind this increase in etching rate are the formation of subwavelength nanoplanes of highly densified material, which align themselves in the direction orthogonal to the laser polarization making the process inherently polarization-dependent 12 , along with changes in the chemical structure, such as the onset of defect like nonbridging oxygen holes (NBOHC) and oxygen deficiency centers (ODC) 10 . Over the last years, FLICE have been successfully used to realize chip integrating features ranging from the micrometric to the centimetric scale, but up to now, the possibilities of making it effective at the nanoscale, in fused silica glass, have not been explored.…”
Section: Introductionmentioning
confidence: 99%